Effectiveness Analysis Of Corn Silk Ointment As A Broad-Spectrum Antibiotic - Susiana, Aisyah; Amriani, Rini; Irfan, Iin Anisa Azzahra; Gemilang, Hanif Semar; Miolo, Zulva Putri Anggita; Awaliyah, Miftah Riska (Hasanuddin University, 2025)
Antibiotic resistance has become a major challenge in wound management, prompting the need for alternative treatments that are both safe and effective. Corn silk (Zea mays L.), a widely available agricultural byproduct, is rich in phenolic compounds known for their anti-inflammatory and wound-healing properties. This study aimed to evaluate the antibacterial effectiveness of corn silk extract-based ointments against Staphylococcus aureus and Escherichia coli, two bacteria commonly associated with wound infections. Corn silk was extracted using the maceration method with 70% ethanol, and the resulting thick extract underwent phytochemical screening. The extract was formulated into ointments at concentrations of 5%, 7%, and 9%, which were then evaluated for their physical characteristics, including organoleptic properties, homogeneity, spreadability, adhesiveness, and pH. Antibacterial activity was assessed using the disk diffusion method, with Bioplacenton® as the positive control. Statistical analysis was performed using One Way ANOVA with IBM SPSS® 25 and Graph Prism® 8. Results indicated that the 7% concentration ointment exhibited the largest inhibition zone, outperforming other concentrations and the positive control, suggesting significant antibacterial activity. Furthermore, all ointment formulations met physical quality standards, ensuring their suitability for topical use. These findings highlight the potential of corn silk extract-based ointments as effective alternatives for managing bacterial skin infections, particularly at a 7% concentration. By utilizing agricultural waste, this study not only addresses sustainability issues but also provides a promising solution to the growing problem of antibiotic resistance. Further research is recommended to explore the underlying mechanisms and expand its applications in clinical settings.